The status of serum 25(OH)D levels is related to breast cancer - Mohammad Momivand; Mahta Razaghi; Farshid Mohammadi; Edris Hoseinzadeh; Roya Najafi-Vosough (Cancer Treatment and Research Communications)
Aim: Breast cancer is the second most common cancer among women and the leading cause of cancer-related mortality in this population. Numerous factors have been identified as either risk factors or protective factors for breast cancer. However, the role of Vitamin D (Vit. D) in breast cancer remains contentious, with conflicting findings in the literature. The present study aimed to compare serum Vit. D levels between women with and without breast cancer. Methods: This cross-sectional study included 40 women diagnosed with breast cancer, referred to the Mahdia Hamadan Radiotherapy Center in 2022. These participants were matched with 40 age- and Vit. D serum level-matched women without breast cancer. Serum Vit. D levels were measured using the ELISA method. Statistical analysis was performed using SPSS version 26, with a significance threshold set at a 95% confidence level. Results: The mean ± standard deviation of serum Vit. D levels in women with and without breast cancer were 31.9 ± 28.27 ng/mL and 37.98 ± 15.89 ng/mL, respectively (P = 0.024). The prevalence of Vit. D insufficiency was 50% in the breast cancer group and 27.5% in the control group, while 50% of the breast cancer group and 72.5% of the control group had sufficient Vit. D levels (P = 0.008). In women with breast cancer, lower Vit. D levels were significantly associated with lower educational (P < 0.001), economic (P < 0.001), and social status (P < 0.001). A weak positive correlation was observed between serum Vit. D levels and patient age (r = 0.162, P = 0.152). Conclusion: The significant difference in serum Vit. D levels between women with and without breast cancer suggests that Vit. D deficiency may be associated with breast cancer risk. These findings support the hypothesis that improving Vit. D status in women could potentially reduce the incidence of breast cancer.